2021
DOI: 10.1038/s41598-021-93043-9
|View full text |Cite
|
Sign up to set email alerts
|

Label-free two-photon imaging of mitochondrial activity in murine macrophages stimulated with bacterial and viral ligands

Abstract: Mitochondria are the metabolic hub of the cell, playing a central role in regulating immune responses. Dysfunction of mitochondrial reprogramming can occur during bacterial and viral infections compromising hosts’ immune signaling. Comparative evaluation of these alterations in response to bacterial and viral ligands can provide insights into a cell’s ability to mount pathogen-specific responses. In this study, we used two-photon excitation fluorescence (TPEF) imaging to quantify reduced nicotinamide adenine d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…TPEF is a linear endogenous fluorescence signal arising from a third-order NLO excitation that scales linearly with the density of NAD(P)H and FAD fluorophores in the focal volume. Its signal can be exploited as an indication of the mitochondrial network location within cells, where metabolic activity is denser ( 40 ). Under near-infrared excitation (a 780-nm pump beam is used in this study), we collected endogenous TPEF signals by NAD(P)H and FAD ranging between 400 and 600 nm ( 41 ) (spectrally separated from CARS and E-CARS signals at 650 ± 20 nm).…”
Section: Resultsmentioning
confidence: 99%
“…TPEF is a linear endogenous fluorescence signal arising from a third-order NLO excitation that scales linearly with the density of NAD(P)H and FAD fluorophores in the focal volume. Its signal can be exploited as an indication of the mitochondrial network location within cells, where metabolic activity is denser ( 40 ). Under near-infrared excitation (a 780-nm pump beam is used in this study), we collected endogenous TPEF signals by NAD(P)H and FAD ranging between 400 and 600 nm ( 41 ) (spectrally separated from CARS and E-CARS signals at 650 ± 20 nm).…”
Section: Resultsmentioning
confidence: 99%
“…The metabolic imaging of immune cells is more recent. Several studies reported the functional assessment of innate and adaptive immune cells in vitro by 2-photon microscopy of NAD(P)H and FAD [111][112][113][114][115][116][117][118][119][120] . These groups successfully performed intensity and lifetime imaging in human neutrophils, T and B cells, mouse immune cells including macrophages, neutrophils, dendritic cells, T and B cells, and several cell lines including THP-1 monocytes, RAW264.7 macrophages, and NK-92 cells, demonstrating that it is a valuable tool in immunometabolism.…”
Section: Fluorescence Lifetime Imaging Microscopy (Flim) Of Nad(p)h A...mentioning
confidence: 99%
“…A comparison of the advantages and disadvantages of each imaging technique can be found in work by Pallen et al [23]. The endogenous molecules that provide label-free multi-photon fluorescence signals in neuronal cultures are FAD and NADH [24,25]. Endogenous multi-photon fluorescence in living cells originating from NADH has already been explored to reveal the mitochondria [26].…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, we took advantage of the properties of label-free non-linear microscopy (combined SHG and multi-photon autofluorescence) to monitor the different growths and differentiations of 50B11 cells on the upper and bottom sides (normal and inverted gravitational orientations) of glass substrates, comparing different time points (24,48, and 72 h).…”
Section: Introductionmentioning
confidence: 99%